2013
DOI: 10.1007/s00404-013-3138-8
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori and anemia with pregnancy

Abstract: Response to iron therapy in cases of iron deficiency anemia in patients without H. pylori infection was better than those infected with H. pylori. H. pylori eradication in the infected cases increased their response to iron therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Interestingly, Nashaat et al. showed that the response to iron therapy in patients with IDA and without H. pylori infection was significantly higher than in patients with active infection. In order to more thoroughly investigate the mechanisms behind this association, Azab et al.…”
Section: Hematological Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, Nashaat et al. showed that the response to iron therapy in patients with IDA and without H. pylori infection was significantly higher than in patients with active infection. In order to more thoroughly investigate the mechanisms behind this association, Azab et al.…”
Section: Hematological Diseasesmentioning
confidence: 99%
“…Similarly, a study by Hamed et al [33] found a difference between infected and noninfected patients concerning the occurrence of dyspepsia and anemia as well as a different distribution of those conditions among patients with different histologic patterns. Interestingly, Nashaat et al [34] showed that the response to iron therapy in patients with IDA and without H. pylori infection was significantly higher than in patients with active infection. In order to more thoroughly investigate the mechanisms behind this association, Azab et al [35] studied the role of hepcidin, a systemic iron homeostasis regulator, showing that H. pylori infection upregulates its serum levels, thus attenuating the response to iron therapy in children with IDA.…”
Section: Hematological Diseases Iron Deficiency Anemiamentioning
confidence: 99%
“…Moreover, a separate case-control study revealed that a significantly higher percentage of women positive for H. pylori stool antigen (HPSA) (indicative of H. pylori infection) developed preeclampsia (PE) with intrauterine growth restriction (IUGR) compared with HPSA-negative women. It is thought that H. pylori-inducediron deficiency anemia (IDA) plays a role in driving IUGR as well [13,14]. These results thus indicated possible etiopathological connections between maternal H. pylori infection and IUGR.…”
mentioning
confidence: 90%
“…Our interest in the role of maternal H. pylori in child's neurodevelopment is founded on two case–control studies, reporting that maternal H. pylori infection could play a role in neural tube defect causation by reducing folate and vitamin B12 concentrations . During pregnancy, H. pylori has been associated with micronutrient deficiencies which are relative resistant to the indicated supplementation . Fetal brain is extremely vulnerable to such micronutrients defects .…”
mentioning
confidence: 99%
“…12,13 During pregnancy, H. pylori has been associated with micronutrient deficiencies which are relative resistant to the indicated supplementation. 14,15 Fetal brain is extremely vulnerable to such micronutrients defects. 16 To the best of our knowledge, no study has examined differences in neurodevelopment between children of H. pylori seropositive vs. seronegative mothers.…”
mentioning
confidence: 99%